Chlamydia infection as a risk factor in ectopic pregnancy: a case control study - George, Angela; S., Shaila (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Chlamydia trachomatis has been linked to 30-50% of all ectopic pregnancies, due to irreversible tissue damage. Hence it is pertinent to explore the risk factors pertaining to Chlamydia infection and ectopic pregnancies. The aim is to study whether Chlamydia infection is a risk factor for ectopic pregnancy in comparison with early intrauterine pregnancy, and study other risk factors in ectopic pregnancy Methods: Case-control study conducted at Sree Avittom Thirunal Hospital, Thiruvananthapuram over a period of six months taking 43 subjects in each group, i.e., cases and controls. An interview followed by collection of venous blood sample was done, which was subjected to Enzyme linked immunoassay test to detect Immunoglobulin G antibodies to Chlamydia. Comparison of qualitative variables such as age, socioeconomic status, history of infertility, history of pelvic inflammatory disease, previous history of ectopic pregnancy, use of IUCD, history of IVF, use of OCP or progesterone only pills and presence of Chlamydia IgG antibodies - between two groups was analyzed by chi-square test and the strength of association expressed in terms of Odds Rati. A p-value <0.05 was considered statistically significant. Results: Out of 86 samples 54 were positive for Chlamydia infection. Subjects with Chlamydia infection had an increased risk of developing ectopic pregnancy. Among the other risk factorshistory of pelvic inflammatory disease and history of infertility were the most significant with Odds of 3.46 and 3.98 respectively. History of oral contraceptive use also had a significant risk associated with developing ectopic pregnancy. Other factors with significant association included, age more than 25 years, Upper Socioeconomic Class, previous ectopic pregnancy and history of IUCD use for more than 5 years. Conclusions: The increased number of Chlamydia infection and its increased risk for developing irreversible sequels such as ectopic pregnancy, it is pertinent to vigilantly diagnose, treat and prevent vaginal infection and pelvic inflammatory disease.